On-line support for students on work placements, lessons learned from a pilot using WebCT, Managed Learning Environment - Cressey, Gill (Proceedings of the International Conference on Networked Learning, 2002)
A project to create on-line support for students on professional development placements in Community, Play and Youth work contexts has provided an ideal situation to carry out a piece of Action Research. The research tracks a number of key players through the process of the introduction of a WebCT course called "Online learning support for students on Fieldwork placements". This includes the unfolding experiences of the course designers, tutors, students and administrators as the course was formulated and introduced. The paper considers a number of very practical issues that have arisen and evaluates the ways in which, and the extent to which, the introduction of this WebCT initiative has added value. Collaboration between administrative, information services and academic staff is crucial for this initiative, and the journey of each of these people in different roles is tracked through the story of the developing project.